Long-term functional changes in an estuarine fish assemblage. Issue 1 (15th August 2015) - Baptista, J.; Martinho, F.; Nyitrai, D.; Pardal, M.A.; Dolbeth, M.
Highlights: Three critical periods from a 30-year period were selected to study the impact of hydrology changes. Functional traits reflected the hydrological disturbance quite well. Hydrological changes affected the structure of the fish community. Changes in hydrology led to the exploration of new micro-habitats and food sources. Estuaries are determinant for restocking many commercial species. Abstract: The functional diversity of the fish assemblages of the Mondego estuary was studied for a discontinuous 30-year period (1988–2012). During this time, hydrological changes occurred due to man-induced alterations and weather extremes. These changes led to alterations in the structure and function of the fish community. Species richness and functional richness decreased over time and the fish community started to explore new micro-habitats and food resources. Before severe hydrological changes, the community was dominated by pelagic, detritivorous and species with wider salinity ranges. After, the community became dominated by demersal, benthic, piscivorous and marine species. During a drought, omnivorous became increasingly important, reflecting greater possibilities of using available feeding resources. We have also found an increase in sub-tropical species throughout the years, which might be related to gradual temperature increases at a global scale. This study also confirmed estuaries as extremely important for restocking several commercial species.